1989
DOI: 10.1128/mcb.9.9.3919
|View full text |Cite
|
Sign up to set email alerts
|

hsp82 is an essential protein that is required in higher concentrations for growth of cells at higher temperatures.

Abstract: hsp82 is one of the most highly conserved and abundantly synthesized heat shock proteins of eucaryotic cells. The yeast Saccharomyces cerevisiae contains two closely related genes in the HSP82 gene family. HSC82 was expressed constitutively at a very high level and was moderately induced by high temperatures. HSP82 was expressed constitutively at a much lower level and was more strongly induced by heat. Site-directed disruption mutations were produced in both genes. Cells homozygous for both mutations did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
464
2
9

Year Published

1996
1996
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(496 citation statements)
references
References 55 publications
21
464
2
9
Order By: Relevance
“…This situation is quite in contrast to the phenomenon observed for eukaryotic cells, the disruption of the two genes for cytosolic Hsp90 being lethal in yeast (22). It is well known that Hsp90 is abundantly expressed in the mammalian cytosol, representing 1-2% of all cytosolic proteins in brain and liver tissues; and hence, Hsp90 is one of the major proteinaceous constituents in the cytosol.…”
Section: Discussioncontrasting
confidence: 40%
See 1 more Smart Citation
“…This situation is quite in contrast to the phenomenon observed for eukaryotic cells, the disruption of the two genes for cytosolic Hsp90 being lethal in yeast (22). It is well known that Hsp90 is abundantly expressed in the mammalian cytosol, representing 1-2% of all cytosolic proteins in brain and liver tissues; and hence, Hsp90 is one of the major proteinaceous constituents in the cytosol.…”
Section: Discussioncontrasting
confidence: 40%
“…5'-ATGAGTAAGAAAGGAACAATCGGG (underlined, first Met codon) and 5'-TCAGAGAAGACGCTGGCTG (underlined, stop codon) for PgHtpG (25); 5'-ATGGATCCGGCTGGTGAAACTTTTGAATTTC (underlined, Ala 2 codon) and 5'-AGCTGCAGATCAACTTCTTCCATCTCGGTG (underlined, stop codon) for yHsc82 (22); and 5'-ATGGCGCGCGAGCTG (underlined, first Met codon) and 5'-TCAGTGTCGCTCCAGGGC (underlined, stop codon) for hTrap1 (23). Amplified DNA fragments were directly inserted into the pTrcHis TOPO expression vector according to the manufacturer's recommendation.…”
mentioning
confidence: 99%
“…While the eubacterial HtpG is dispensable under normal growth conditions (Bardwell and Craig, 1988), the Hsp90 in eukaryotes is one of the most abundant (~ 1-2% of total cytosolic proteins) and essential protein for cell viability (Borkovich et al, 1989). This means in eukaryotes Hsp90 could have many diverse cellular functions other than chaperoning folding intermediates.…”
Section: Ii41122 the Hsp90 Chaperone Systemmentioning
confidence: 99%
“…The budding yeast Saccharomyces cerevisiae (S. cerevisiae) was the first organism for which it was shown that Hsp90 is essential for viability [12]. This genetically easily manipulable organism has two genes, HSC82 and HSP82, which encode two 95% identical Hsp90 proteins.…”
Section: Introductionmentioning
confidence: 99%